2004
DOI: 10.1111/j.1365-2354.2003.00435.x
|View full text |Cite
|
Sign up to set email alerts
|

The European Organization for Research and Treatment of Cancer QLQ-C30: an examination into the cultural validity and reliability of the Turkish version of the EORTC QLQ-C30

Abstract: The Turkish version of the European Organization for Research and Treatment of Cancer Quality of Life Core Questionnaire version 2.0 (EORTC QLQ-C30 v.2.0) has started to be used in clinical trials recently. The objective of the study was to evaluate the validity and reliability of the Turkish version of the EORTC QLQ-C30 v.2.0 and the correlation between the Karnofsky Performance Scale (KPS) and the EORTC QLQ-C30. Two hundred and two lung cancer patients were included in the study between January and March 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
79
2
7

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(109 citation statements)
references
References 27 publications
(28 reference statements)
15
79
2
7
Order By: Relevance
“…The cognitive functioning scale showed poor internal consistency at all levels of analysis. Our findings were similar to several other validation studies involving the EORTC QLQ-C30 in many Asian countries and language settings such as China (Cheng et al, 2011), Indonesia (Perwitasari et al, 2011), Singapore (Luo et al, 2005), Korea (Yun et al, 2004), Turkey (Guzelant et al, 2004), Iran (Hajebrahimi et al, 2013), and Malaysia (breast cancer) (Yusoff N et al, 2010). All these studies reported a poor internal consistency coefficient for the cognitive functioning scale (Cronbach's alpha ranges from 0.19 to 0.67).…”
Section: Discussionsupporting
confidence: 91%
“…The cognitive functioning scale showed poor internal consistency at all levels of analysis. Our findings were similar to several other validation studies involving the EORTC QLQ-C30 in many Asian countries and language settings such as China (Cheng et al, 2011), Indonesia (Perwitasari et al, 2011), Singapore (Luo et al, 2005), Korea (Yun et al, 2004), Turkey (Guzelant et al, 2004), Iran (Hajebrahimi et al, 2013), and Malaysia (breast cancer) (Yusoff N et al, 2010). All these studies reported a poor internal consistency coefficient for the cognitive functioning scale (Cronbach's alpha ranges from 0.19 to 0.67).…”
Section: Discussionsupporting
confidence: 91%
“…Turkish validity and reliability were assessed by Guzelant et al (2004). EORTC QLQ-C30 has three subscales: "general well-being (QL2)", "functional difficulties" and "symptoms".…”
Section: Data Collection Toolsmentioning
confidence: 99%
“…Turkish validity and reliability of the scale was conducted by Güzelant and his friends (2004) and Cronbach alpha coefficient was found to be ≥0.70. [32,33] Validity Studies Linguistic Validity and Content Validity: First of all, original scale has been translated from English to Turkish by five experts (one psychologist, one psychological consultancy specialist, two experts specialized in the nursing related with mental health and diseases, one teacher who is graduated from English Language and Literature Division) by conducting a group translation. The Turkish form which was obtained after the translation was further translated from Turkish to English by two translators, with English being their mother tongue, who have been living in Turkey for many years as a common study conducted by them.…”
Section: Data Collection Toolsmentioning
confidence: 99%